Matrix Metalloproteinase-3 Is Increased and Participates in Neuronal Apoptotic Signaling Downstream of Caspase-12 during Endoplasmic Reticulum Stress - Kim, Eun-Mee (American Society for Biochemistry and Molecular Biology, 2010)
Although endoplasmic reticulum (ER) stress-induced apoptosis has been associated with pathogenesis of neurodegenerative diseases, the cellular components involved have not been well delineated. The present study shows that matrix metalloproteinase (MMP)-3 plays a role in the ER stress-induced apoptosis. ER stress induced by brefeldin A (BFA) or tunicamycin (TM) increases gene expression of MMP-3, selectively among various MMP subtypes, and the active form of MMP-3 (actMMP-3) in the brain-derived CATH.a cells. Pharmacological inhibition of enzyme activity, small interference RNA-mediated gene knockdown, and gene knock-out of MMP-3 all provide protection against ER stress. MMP-3 acts downstream of caspase-12, because both pharmacological inhibition and gene knockdown of caspase-12 attenuate the actMMP-3 increase, but inhibition and knock-out of MMP-3 do not alter caspase-12. Furthermore, independently of the increase in the protein level, the catalytic activity of MMP-3 enzyme can be increased via lowering of its endogenous inhibitor protein TIMP-1. Caspase-12 causes liberation of MMP-3 enzyme activity by degrading TIMP-1 that is already bound to actMMP-3. TIMP-1 is decreased in response to ER stress, and TIMP-1 overexpression leads to cell protection and a decrease in MMP-3 activity. Taken together, actMMP-3 protein level and catalytic activity are increased following caspase-12 activation during ER stress, and this in turn plays a role in the downstream apoptotic signaling in neuronal cells. MMP-3 and TIMP-1 may therefore serve as cellular targets for therapy against neurodegenerative diseases.